A Multi-Modality Pelvic Anatomy Education Program for Ob/Gyn Residents [15O]. (May 2018) - Suh, Christina; Mulheron, George; O'Brien, Devon; Esguerra, Cybill; Pradhan, Archana; Balica, Adrian
Abstract : INTRODUCTION: Understanding pelvic anatomy is essential to training as an ob/gyn. In most residency programs, residents learn anatomy through self-guided reading and direct experiences in the operating room, which can be limited by time constraints and patient safety concerns. The purpose of our study was to develop and assess a novel pelvic anatomic education program for residents. METHODS: We utilized three different learning modalities: cadaveric dissection on unused cadavers from our medical school's anatomy course, clay models of the pelvic floor, and didactic lectures. The cadaver dissection was presented in a "mock surgery" format. Learning objectives and relevant procedures were established for each year of training: abdominal wall anatomy and cesarean section for first years, pelvic spaces and abdominal hysterectomy for second years, presacral space and sacrocolpopexy for third years, and pelvic neuroanatomy for fourth years. Participants completed before and after multiple choice tests and a qualitative survey. RESULTS: 16 residents from all 4 years of training were recruited to participate in the program. The average pre-test score was 45% and average post-test score was 50%, (p=0.22). The majority of participants strongly agreed that the program was interesting (67%), enhanced their understanding of pelvic anatomy (73%), and increased their confidence in the operating room (53%). CONCLUSION: Our multi-modality pelvic anatomy program improved residents' anatomic knowledge (although this was not statistically significant) and was well received as a clinically applicable educational activity. The cadaveric lab mirrored the gynecological surgical curriculum of our residency and was cost efficient through collaboration with the anatomy department.